Jesus in Disguise: Animated and Fantasy Films as Media for Christian Mission - Ryanto Adilang (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
Christian mission has undergone many shifts from the time of the apostles to the present day. However, the traditional understanding of Christian mission is still often found in many places. Christian missions that still have a Christianization flavor are of course no longer relevant in the midst of a pluralistic society. Forcing a traditional Christian mission in the context of changing times will certainly be read as a radical action. So a modern mission approach is needed. Christian mission approach that will not ignite the fire of conflict but also does not lose the identity of preaching the gospel. This study uses a qualitative method with a descriptive approach. This research was written as an attempt to find a Christian Mission method that would not hit the fence of inter-religious tolerance. Therefore, in this research, theories related to Christian Mission and Evangelism and other relevant theories will be used. The results of this study are expected to maximize efforts to carry out Christian missions without having to interfere with the faithful activities of other religious people. The Christian mission will continue but will not lead to Christianization. There will be a clear distinction between Mission and imposing beliefs on others.